Regional distribution of glucose-6-phosphate dehydrogenase deficiency in Turkey and evaluation of clinical findings: a multicenter study - Sayın, Selim; Kılıçaslan, Emrah; Yıldırım, Murat; Özgür, Gökhan; Kaptan, Kürşat; Beyan, Cengiz; Aylı, Meltem (The European Research Journal, 2022)
Objectives: The single most inherited enzyme deficiency is that of glucose-6-phosphate dehydrogenase (G6PD) with a presence in almost 400 million of theworld’spopulation. Thenumber of reported G6PD mutations is 186. Furthermore, geographical location is a determining factor for the prevalence of G6PD. Therefore, much of the existing epidemiological literature concerning this issue in Turkey has reported data specific to cities and regions. The purpose of this study was to examine G6PD deficiency in a sample of subjects. Outcome measures reported in this study include the clinical factors as sociated with the deficiency, as well as in geographical dispersion across regional locations in Turkey. Methods: This is a retrospective, cross-sectional study. The sample comprised 308 subjects with a G6PD diagnosis. Data collection commenced in January 2011, and was completed by May 2020. Results: In Turkey, the Mediterranean region has the greatest prevalence of G6PD enzyme deficiency. Subjects presenting with this deficiency were also diagnosed with haemolytic anaemia that was attributed to favism. Subsequently, drug and neonatal hyperbilirubinemia-induced haemolysis ensued. Over 90% of subjects diagnosed with a critical G6PD deficiency and recurrent haemolysis were allocated to the Class II variant. Conclusions: The Mediterranean, along with Agean and Marmara regions are where the highest prevalence of G6PD enzyme deficiency are observed. Favism-induced haemolytic anaemia is the most often identified clinical precursor to diagnosis of G6PD deficiency in Turkey. The most common clinical feature after this condition is drug related haemolysis and the onset neonatal hyperbilirubinemia.